Contemporary enzyme based technologies for bioremediation: A review. (15th March 2018) - Sharma, Babita; Dangi, Arun Kumar; Shukla, Pratyoosh
Abstract: The persistent disposal of xenobiotic compounds like insecticides, pesticides, fertilizers, plastics and other hydrocarbon containing substances is the major source of environmental pollution which needs to be eliminated. Many contemporary remediation methods such as physical, chemical and biological are currently being used, but they are not sufficient to clean the environment. The enzyme based bioremediation is an easy, quick, eco-friendly and socially acceptable approach used for the bioremediation of these recalcitrant xenobiotic compounds from the natural environment. Several microbial enzymes with bioremediation capability have been isolated and characterized from different natural sources, but less production of such enzymes is a limiting their further exploitation. The genetic engineering approach has the potential to get large amount of recombinant enzymes. Along with this, enzyme immobilization techniques can boost the half-life, stability and activity of enzymes at a significant level. Recently, nanozymes may offer the potential bioremediation ability towards a broad range of pollutants. In the present review, we have described a brief overview of the microbial enzymes, different enzymes techniques (genetic engineering and immobilization of enzymes) and nanozymes involved in bioremediation of toxic, carcinogenic and hazardous environmental pollutants. Highlights: Microbial enzymes involved in degradation of various toxic pollutants. Major biodegrdative enzymes over-expressed using recombinant DNA technology. Enzyme immobilization techniques increase the half-life, stability and activity of enzymes. Nanozymes used for bioremediation purpose.